Analisis Daya Dukung Fondasi pada Gedung Perkantoran Universitas Jambi: Foundation Bearing Capacity Analysis On Jambi University Office Building - Ramadhanis, Ulfa Dayini; Dwina, Dila Oktarise; Nuklirullah, M. (Jurnal Rekayasa Infrastruktur HEXAGON, 2024)
Several pile caps changed shape and size due to the addition of pile columns on some pile caps of the Jambi University office building. The pre-planned pile caps depth changed to 11-19,5 m from 30 m at each point. The change was due to the existing land conditions on the field that did not support the original foundation plan. For the construction of the building to stand firm, the foundation plan must adapt to the field conditions. The research method used is the evaluation method, which performs an analysis of the foundation-bearing capacity after the occurrence of changes. It consists of three stages: the data collection stage, the analysis stage, and the decision-making stage. At the critical depth achieved, the days of axial support pressure 744,107 kN, the traction axial support power 169,16 kN, and the P6A type pillar group bearing capacity 11161,6 kN. The foundation is said to be able to withstand the upper structural load demonstrated by the results of a single pillar analysis when Qall > upper structure load worth 218.867,458 kN > 157924,94 kN and on the group pillar is said safe when the security factor obtained > the minimum security factor. The results concluded that the foundation bearing capacity analysis on Jambi University Office Building is safe and able to withstand the load of structures above the building.